Leptin levels are associated with multiple sclerosis risk. (January 2021) - Biström, Martin; Hultdin, Johan; Andersen, Oluf; Alonso-Magdalena, Lucia; Jons, Daniel; Gunnarsson, Martin; Vrethem, Magnus; Sundström, Peter
Background: Obesity early in life has been linked to increased risk of developing multiple sclerosis (MS). Leptin and insulin are both associated with obesity, making them suitable candidates for investigating this connection. Objective: To determine if leptin and insulin are risk factors for relapsing–remitting multiple sclerosis (RRMS). Methods: In this nested case–control study using blood samples from Swedish biobanks, we compared concentrations of leptin and insulin in 649 individuals who later developed RRMS with 649 controls matched for biobank, sex, age and date of sampling. Only pre-symptomatically drawn samples from individuals below the age of 40 years were included. Conditional logistic regression was performed on z -scored values to calculate odds ratios (ORs) with 95% confidence intervals (CIs). Results: A 1-unit leptin z -score increase was associated with increased risk of MS in individuals younger than 20 years (OR = 1.4, 95% CI = 1.1–1.9) and in all men (OR = 1.4, 95% CI = 1.0–2.0). In contrast, for women aged 30–39 years, there was a lower risk of MS with increased leptin levels (OR = 0.74, 95% CI = 0.54–1.0) when adjusting for insulin levels. Conclusion: We show that the pro-inflammatory adipokine leptin is a risk factor for MS among young individuals.